An Analysis of Wheat Farming: Calculations and Perceptions - Zebua, Damara Dinda Nirmalasari; Priyanto, Sony Heru; Sunaryanto, Lasmono Tri (Universitas Sebelas Maret, 2019)
National diversification of wheat-based food has been put into practice. Public consumption of flour-based food, such as noodles and bread, is in great demand. This study aims to determine the calculations, perceptions and attitudes of farmers towards wheat farming, considering that Indonesia is a non-wheat developing country. This qualitative descriptive research using in-depth interviews with 7 informants and observation methods was conducted in Klaten and Demak Regencies. In analyzing the data, this study used an interactive analysis model including data reduction, data presentation and conclusion drawing. The results show that: 1) based on farmers' calculations, wheat farming is financially not profitable to farmers because the products harvested are not worth the expense; 2) farmers' calculations affect farmers' perceptions which shifted to negative perceptions that wheat farming is not as promising as other farming businesses. Despite the negative perceptions, wheat farming has provided a valuable experience for farmers which is shown by their pride and pleasure and 3) the majority of farmers are not interested in wheat farming, which is shown by their attitude of not being able to accept wheat farming, while other farmers behave otherwise, indicated by their willingness to recommence wheat planting testing. Further research may examine: 1) how to change the culture of rice farming into culture of wheat farming; 2) how to change subsistence rice farming into enterprise and 3) how to change rice farming as social activities to rice farming as business activities.